Selective Neck Dissection and Survival in Pathologically Node-Positive Oral Squamous Cell Carcinoma - Shimura, Shunichi; Ogi, Kazuhiro; Miyazaki, Akihiro; Shimizu, Shota; Kaneko, Takeshi; Sonoda, Tomoko; Kobayashi, Junichi; Igarashi, Tomohiro; Miyakawa, Akira; Hasegawa, Tadashi; Hiratsuka, Hiroyoshi (Cancers, 2019)
The most important prognostic factor in oral squamous cell carcinoma (OSCC) is neck metastasis, which is treated by neck dissection. Although selective neck dissection (SND) is a useful tool for clinically node-negative OSCC, its efficacy for neck node-positive OSCC has not been established. Sixty-eight OSCC patients with pN1–3 disease who were treated with curative surgery using SND and/or modified-radical/radical neck dissection (MRND/RND) were retrospectively reviewed. The neck control rate was 94% for pN1–3 patients who underwent SND. The five-year overall survival (OS) and disease-specific survival (DSS) in pN1-3 OSCC patients were 62% and 71%, respectively. The multivariate analysis of clinical and pathological variables identified the number of positive nodes as an independent predictor of SND outcome (OS, hazard ratio (HR) = 4.98, 95% confidence interval (CI): 1.48–16.72, p < 0.01; DSS, HR = 6.44, 95% CI: 1.76–23.50, p < 0.01). The results of this retrospective study showed that only SND for neck node-positive OSCC was appropriate for those with up to 2 lymph nodes that had a largest diameter ≤3 cm without extranodal extension (ENE) of the neck and adjuvant radiotherapy. However, the availability of postoperative therapeutic options for high-risk OSCC, including ENE and/or multiple positive lymph nodes, needs to be further investigated.